Les chansons et musiques populaires innues : contexte, signification et pouvoir dans les expériences sociales de jeunes Innus - Audet, Véronique (Recherches amérindiennes au Québec, 2005)
This article presents popular Innu musical expressions as voices that serve to reaffirm Innu identity and revitalize Innu society and culture. These songs in the Innu language are inspired by various musical trends such as country, rock, folk and pop, as well as Innu, Pan-Indian, Christian and Quebecois traditions. They have been created, practiced and renewed since the second half of the twentieth century, accompanying the often radical events, movements and transformations that have marked Innu social and cultural life. Contemporary Innu youth, like their predecessors, are the primary conveyers of this expressive movement which they use to participate in the daily life of their communities, and reaffirm their identity, their experiences and their preoccupations, thus contributing to the revitalization of their world and the Innu “way of being”. We present some of the singers, groups and songs that are representative of contemporary Innu musical expression and who have had a significant impact within their society. This provides a sensitive understanding of the context, the significance and the power of these expressions.
Publisher: Recherches amérindiennes au Québec